Inal Mama : sagrada y profana - Lopes, Eduardo (Naira Cine, 2008)
The saga of the coca leaf is interwoven from what the Bolivian documentary "Inal Mama" presents as the routes of the sacred and the profane: the San Pedro prison and the Guarani community of Tentayapi. These two axes present nodal aspects of the coca leaf in different cultural spaces: as drugs, medicine, exploitation, religion, injustice and instrument of power. --